(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2023)
This study investigated the social media posts of the media spokespersons of the three front line presidential candidates in the 2023 presidential election in Nigeria with the aim of assessing their use of verbal hygiene, or the lack thereof, in their social media posts. The study examines how these representatives take to mudslinging instead of persuasion which political discourses have been touted to employ. Theoretical framework for the study is Brown and Levinson’s Politeness theory. Data for the study comprised twelve (12) social media posts made by the All Progressive Congress, People’s Democratic Party and Labour party spokespersons for the 2023 presidential election. They were purposely selected and analysed in line with the theory for the study. Findings reveal that these spokespersons of the presidential candidates of All Progressive Congress, People’s Democratic Party and Labour Party employed bald on record impoliteness, positive impoliteness and negative impoliteness to damage the face of opposition parties’ presidential candidates. The LP spokesperson employed negative impoliteness two times, positive impoliteness once and bald on record impoliteness two times in his social media posts. The PDP spokesperson employed negative impoliteness two times, and bald on record impoliteness two times, but did not use positive impoliteness in the social media posts analysed in the current study. The APC spokesperson employed negative impoliteness two times, positive impoliteness two times and bald on record impoliteness two times. None of the spokespersons used off-record impoliteness or withhold impoliteness. The research concludes that these spokespersons practiced mudslinging as the words they used on the opposition were certainly not verbally hygienic.